Validation of the name Heliconia ×rauliniana (Heliconiaceae) - Alvarenga Braga, Joao Marcelo; Joffily, Ana (Phytotaxa, 2014)
In the protologue, two specimens of Heliconia collected on different dates and locations were designated as a single holotype. Consequently, Heliconia ×rauliniana (pro sp.) must be considered an invalidly published name. This natural hybrid is widely cultivated and used in worldwide floriculture trade. The present work proposes to validate the name H. ×rauliniana.